2009
DOI: 10.1124/dmd.108.024224
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Gender-Divergent UDP-Glucuronosyltransferase mRNA Expression in Mouse Liver and Kidney

Abstract: ABSTRACT:UDP-glucuronosyltransferases (UGTs) catalyze the addition of glucuronic acid to endo-and xenobiotics, increasing hydrophilicity and enhancing elimination. Gender-divergent glucuronidation rates are observed in humans and rats, and gender differences in UGT mRNA levels have been observed in rodents. The purpose of this study was to establish the hormonal regulation of genderdependent Ugt mRNA expression in mouse liver and kidney. Therefore, three mouse models were used to characterize the involvement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 33 publications
5
47
0
Order By: Relevance
“…We found that seven of nine (77.8%) Ugt genes on the array were differentially expressed at q values Յ0.01. Ugt genes were found to be exclusively male biased, which is consistent with the finding that Ugt expression is regulated by male GH production in the liver (8). ABC transporters affect the disposition of many endo-and xenobiotics.…”
Section: Sex-dependent Differences In Gene Expression In Liver: Physisupporting
confidence: 77%
“…We found that seven of nine (77.8%) Ugt genes on the array were differentially expressed at q values Յ0.01. Ugt genes were found to be exclusively male biased, which is consistent with the finding that Ugt expression is regulated by male GH production in the liver (8). ABC transporters affect the disposition of many endo-and xenobiotics.…”
Section: Sex-dependent Differences In Gene Expression In Liver: Physisupporting
confidence: 77%
“…However, Ugt2b1 mRNA levels decreased between 3 and 27 months of age in both genders. A previous study (Buckley and Klaassen, 2009) reported that the regulation of Ugt2b1 expression in mouse liver was attributable to male-pattern growth hormone secretion. This may explain the dramatic decreases in Ugt2b1 levels for male mice with aging and less dramatic decreases for female mice.…”
Section: Discussionmentioning
confidence: 99%
“…Gender-divergent expression regulated by growth hormone secretion was reported for P450s (Pampori and Shapiro, 1999), Sults (Liu and Klaassen, 1996;Alnouti and Klaassen, 2006), Ugts (Buckley andGsts (Srivastava andWaxman, 1993;Knight et al, 2007), as well as xenobiotic transporters (Tanaka et al, 2005;Cheng et al, 2006;Maher et al, 2006). Because of the altered sex hormone and growth hormone levels in old age (Rudman et al, 1990;Bjørnerem et al, 2004), it is important to investigate the gender differences in XPG expression during aging.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear why the remaining differences in constitutive expression occur in one gender but not the other. This laboratory has previously investigated gender-divergent regulation of Ugt and Sult enzymes (Buckley and Klaassen, 2009b;Alnouti and Klaassen, 2011). Sult enzymes are critically regulated by the stimulatory effects of estrogens and growth hormone secretion patterns and suppressed by androgens.…”
Section: Transcription Factor-gene Interactionsmentioning
confidence: 99%